Evaluation effects of alternative substrates for soilless cultivation of strawberry (Fragaria x ananassa) - García-López, Daniel A.; Cruz-Ortega, Raquel (Nexo Revista Científica, 2023)
Strawberry is one of the major cultivations in Mexico, nonetheless, low development of planting techniques reduces fruit quality. The present research aimed to evaluate alternative substrates for soilless cultivation of strawberry, variety festival (Fragaria x annanasa). Four substrates were evaluated to achieve the goal: T1 coconut fiber substrate, T2 volcanic rock “tezontle”, T3 coconut fiber 50 % volcanic rock “tezontle” 50 %, and T4 soil as control. To compare the substrates, some properties that people chose in the fruit were selected: number of fruits per plant, fruit weight, fruit size, and Brix degrees (° Brix). The ° Brix did not show differences among the treatments; however, under T2 and T3 the best results were observed in terms of the number of fruits per plant, fruit weight and fruit size, which are considered remarkable market fruit qualities. In all the cases, T4 showed the lowest values in comparison to the other substrates. In conclusion, due to its low-cost volcanic rock alone or combined with coconut fiber could be used as a promising substrate for the production of strawberries; however, further work is needed to optimize other factors such as fertilization regimes and irrigation to reduce the production cost in a soilless production system.